Phytochemical, Acute toxicity, and Antibacterial Activity of Tamarindus indica Against Antimicrobial-Resistant Staphylococcus aureus - Nazuwa Dominic; Ewansiha Uyi Joel; AbdulAzeez Mumsiri Abaka; Ibrahim Yau (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The escalating public health crisis of antimicrobial resistance (AMR), driven by pathogens like methicillin-resistant Staphylococcus aureus (MRSA), demands an urgent expansion of the therapeutic arsenal. This study provides a comprehensive scientific validation of Tamarindus indica L., a plant with extensive ethnobotanical uses, by systematically evaluating its phytochemical composition, antibacterial efficacy, and acute toxicity profile. Phytochemical analysis revealed that methanol extraction was superior to n-hexane, yielding a rich array of bioactive compounds from the leaves, including alkaloids, flavonoids, saponins, and phenolic compounds. Quantitative assessment confirmed substantial levels of key metabolites, with saponins (550–1400 mg/100g), total phenolics (800–2000 mg/100g), and flavonoids (450–1100 mg/100g) being the most abundant. Antibacterial assays demonstrated that the methanolic extract possessed potent, strain-specific activity against clinical isolates of S. aureus. A notable finding was the significant susceptibility of one strain (SaD), which showed a zone of inhibition of 23.00 mm at 80 mg/mL, exceeding the activity of the cefoxitin control. The methanol fruit extract exhibited Minimum Inhibitory Concentration (MIC) values between 4.69 and 9.38 mg/mL. Crucially, the Minimum Bactericidal Concentration (MBC) was identical to the MIC for most strains, indicating a primarily bactericidal, rather than bacteriostatic, mode of action. In stark contrast, the n-hexane extract showed minimal efficacy, highlighting the critical influence of solvent polarity on the recovery of antibacterial constituents. A pivotal component of this research was the toxicological evaluation. An acute oral toxicity study conducted in rats established an excellent safety profile, with no mortality or significant adverse effects observed at the limit dose of 5000 mg/kg, classifying the extract as practically non-toxic according to OECD guidelines. This finding confirms a wide therapeutic window for potential applications. In conclusion, this study definitively links the traditional use of Tamarindus indica to a scientifically verified, bactericidal phytochemical profile effective against S. aureus and a compelling safety margin. These results firmly position T. indica as a promising candidate for the development of standardized herbal medicines to address the growing threat of antibiotic-resistant infections.